'I am but a livery servant': examining ruptures in master-servant relationships of the nineteenth-century country house. (4th May 2019) - Eales, Sally
Abstract : The balance of power in nineteenth-century country estates was firmly weighted in the employer's favour, making it difficult for servants to carve out an identity, find a voice, or establish self-worth. Their characters, morality and conduct were often problematized by the upper classes, and they were frequently derided, as Davidoff (1993) suggests, for 'having very ambivalent attitudes towards their employers'. Applying discourse analysis to data derived from nineteenth-century servant letters uncovered in two archived collections (the Savernake Estate and Mote House) this article reveals the complex tensions and ambiguities that characterised working relations between masters and servants in such households. By focussing explicitly on how servants managed perceptions of themselves in moments of rupture this article considers how their narratives can be re-conceived as active dialogues in which different representations of the self and the complex layers of the domestic service relationship are continually and creatively re-formulated.